Growth, Development And Productivity Indicators Of Bread Wheat Lines Established In Local Conditions - Dilmurodov Sherzod Dilmurodovich.; Jabarov Farrukh Odirovich (Zien Journals, 2023)
It is known that today, the food problem, the increase of the population, the decrease of cultivated land areas, and the destruction of ecology are increasing the demands for new varieties of agricultural crops. That is why the government of our republic pays great attention to the field of selection and seed production. In this context, studies were conducted on 35 varieties and lines of soft wheat in the laboratory of genetics and selection of spiked grain crops of the Southern Agricultural Research Institute. "Shams" and "Antonina" varieties, which are planted in large areas of our republic, were taken as model varieties. As a result of the research, wheat lines with a short growing season and high productivity were selected.
Keywords: autumn soft wheat; vegetation period; plant height